A study on relationship of age at first coitus and number of conceptions with the development of uterine cervical dysplasia in women undergoing VIA screening at community health centre, Muradnagar, U.P., India - Vashist, Sunita; Singh, Narendra (International Journal Of Community Medicine And Public Health, 2018)
Background: Cancer of cervix is a common cancer that affects Indian women physically psychologically, socially and financially. The disease affects not just the women but also her family and society. Development of cervical dysplasia is highly associated with age of first coitus and number of conception of women. This study was designed to study the correlation between age of first coitus and number of conceptions in women with development of uterine cervical dysplasia. Methods: This study was done at the Community Health Centre (CHC), Muradnagar. It was a cross-sectional study done by using VIA (visual inspection using acetic acid) technique on uterine cervix on 1250 women aged above 30 years of age attending gynaecology OPD of CHC, Muradnagar, Ghaziabad, U.P. Purposive sampling was used to enrol all the women who were attending the gynaecology OPD at CHC and were coming in the eligibility criteria. Results: Out of 1250 women 14 were found to be VIA positive, out of which 4 cases came out to be positive for dysplasia after doing biopsy under colposcopy. Conclusions: Development of cervical dysplasia is highly correlated with early age at first coitus and more number of conceptions in women. As cervical dysplasia is highly associated with early age at first coitus and more conceptions, so more screening for cervical dysplasia required in women having first coitus at early age and having more conceptions.